Globalization of Corporate Covernance: The American Influence on Dismissal Performance Sensitivity of European CEOs - Jochen A. Jungeilges; Lars Oxelheim; Trond Randoy (Research Institute of Industrial Economics (IFN), 2010)
This study examines how globalization of corporate governance practices influence the risk of European CEOs being dismissed. We argue that the harsh monitoring of the American corporate governance system spills over to the rest of the world as a result of this globalization. We focus on direct and indirect American influence on the dismissal performance sensitivity among the 250 largest European publicly listed firms. The indirect influence is assumed to materialize via European firms cross-listing on U.S. exchanges, whereas the direct influence is assumed to appear as a result of European firms hiring of American independent board members. Both sources of influence are hypothesized to result in increased dismissal performance sensitivity. The empirical results show a significant increase in the dismissal sensitivity in poorly performing companies with American board membership whereas no significant increase is found from cross-listing in the U.S.
Keywords: G15; G18; G32; M14; M16; M52; 330; CEO dismissal; Performance sensitivity; Globalization; Corporate governance; Foreign board membership; Institutional contagion; Führungskräfte; Kündigung; Corporate Governance; Unternehmenskultur; Zweitlisting; Vorstand; International; EU-Staaten; USA